Exact-differentiation-based leak detection and isolation in a plastic pipeline under temperature variations. (June 2016) - Delgado-Aguiñaga, J.A.; Begovich, O.; Besançon, G.
Abstract : Highlights: A new temperature-dependent modeling to detect and locate a single leak. Exact-differentiation-based observer for leak detection and isolation. Experimental results with real-data are compared with traditional approaches. Abstract: This paper presents an algorithm to detect and locate a leak in a plastic pipeline which carries pressurized water, taking temperature variations into account . The algorithm is based on an appropriate modeling, as well as a Robust Exact Differentiation method for state variables and leak parameters estimation. The model includes temperature dependence in several parameters ( friction factor and Equivalent Straight Length typically), and the exact differentiation method is based on so-called Higher-Order Sliding Modes . The algorithm only considers measurements coming from pressure head and flow rate sensors located at the pipeline ends, while temperature variations are monitored via a sensor in the upstream tank feeding the pipeline. Experimental results finally illustrate the performance of this algorithm, and more particularly in comparison with the case when temperature variations are not considered.